Compositional Safety Logics - Andersen, Jørgen H.; Larsen, Kim G. (BRICS Report Series, 1997)
In this paper we present a generalisation of a promising compositional model-checking technique introduced for finite-state systems by Andersen in [And95] and extended to networks of timed automata by Larsen et al in [LPY95a, LL95, LPY95b, KLL+97a]. In our generalized setting, programs are modelled as arbitrary (possibly infinite-state) transition systems and verified with respect to properties of a basic safety logic. As the fundamental prerequisite of the compositional technique, it is shown how logical properties of a parallel program may be transformed into necessary and sufficient properties of components of the program. Finally, a set of axiomatic laws are provided useful for simplifying formulae and complete with respect to validity and unsatisfiability.